Edukasi Pengenalan Investasi bagi Generasi Z - Fitri, Aida; Wiratama, Muhammad Jaka; Bachtiar, Fandi; Fuad , Ammar; Harbiyah G (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
The investment socialization carried out at the Economic Building located at Jalan Muhammadiyah, Lueng Bata District, Banda Aceh City aims to provide knowledge and insight regarding investment. This activity was carried out by the Lecturer Team of the Entrepreneurship Study Program, Faculty of Economics, Muhammadiyah University of Aceh. Training participants demonstrated significant improvements in knowledge and regarding investments. The survey results showed that 80% of participants were interested in starting to invest in both Islamic and conventional shares, which could increase participants' income and increase their insight and utilize opportunities and time more efficiently. The expected output from this community service activity is increasing the insight and knowledge of generation Z, especially teenagers aged <30 years, to avoid fraudulent investments and be able to choose more appropriate investments. Apart from that, this activity aims to encourage them to develop the knowledge gained from academics, the results of this activity will be published in a journal.